Construction of Dirac Delta Function from the Discrete Orthonormal Basis of the Function Space - Lamichhane, Hari Prasad (Himalayan Physics, 2017)
Orthonormal basis of the function space can be used to construct Dirac delta function. In particular, set of eigenfunctions of the Hamiltonian operator of a particle in one dimensional infinite potential well forms a non-degenerate discrete orthonormal basis of the function space. Such a simple basis set is suitable to study closure property of the basis and various properties of Dirac delta function in Physics graduate lab. The Himalayan Physics Vol. 6 & 7, April 2017 (54-57)